The association of mindfulness with athletes’ fear of failure: the mediating roles of perfectionism and ego-depletion - Zhong, Zhangyi; Jiang, Hongyu; Wang, Huilin (Frontiers in Public Health, 2025)
IntroductionFailure is an inevitable part of an athlete’s career, often bringing emotional setbacks that may affect performance and long-term development. This study adopted a cross-sectional design using convenience and snowball sampling to explore how mindfulness relates to athletes’ fear of failure.MethodsA total of 285 valid responses were gathered from university athletes, youth training centers, and sports schools across Hunan, Hubei, and Sichuan provinces. Structural equation modelling (AMOS v26) was employed to test the proposed model.ResultsThe findings indicated that mindfulness was negatively associated with perfectionism and ego-depletion. In contrast, both perfectionism and ego-depletion were positively related to fear of failure—that is, individuals with higher levels of perfectionism experienced greater ego-depletion. Furthermore, both perfectionism and ego-depletion mediated the relationship between mindfulness and fear of failure. These results suggest that athletes with higher levels of mindfulness tend to exhibit lower levels of perfectionistic tendencies and ego-depletion, and consequently experience less fear of failure.ConclusionBased on these findings, it is recommended that mindfulness training be incorporated into regular athletic programs, supported by adequate resources to promote athletes’ mental well-being and competitive resilience. Coaches and family members should adopt more supportive and encouraging attitudes, reducing the psychological harm athletes may experience after failure. Moreover, athletes should acknowledge and accept their fear of failure, and seek professional support in a timely manner when troubled by negative psychological states, to ensure both physical and mental well-being.